Kemampuan Guru Ipa Kelas VIII SMP Swasta Islam Di Surakarta Dalam Penerapan Kurikulum 2013 Pada Semester Genap Tahun Ajaran 2014/2015 - , ANWAR; , Dra. Hariyatmi, M.Si (2015)
This research aims to know the problems in implementing the IPA teacher curriculum private JUNIOR HIGH SCHOOL in Surakarta 2013 academic year 2014/2015. This research is qualitative dskriptif research id estresearch by seeking out as many then draw conclusions from all sources are obtained in the form of a sentence. Research data was obtained from the preparation of the RPP made by IPA teacher observation, implementation of the RPP in the process of learning the IPA even semester academic year 2014/2015 and the interview against the teachers a curriculum on the implementation of the IPA 2013. Results of the study preparation of the RPP curriculum 2013 that the ability of teachers still experience constraints in the list the learning objectives (58,33%). The ability of teachers in the implementation of the RPP in the process of learning the IPA for the preliminary activities namely conducting salam, apersepsi, motivation, and deliver learning objectives (33,33%), applying scientific methods (58,33%), applying the scientific approach to learning (58,33%), id est cover activities implement measures cover (58,33%).Constraints in the implementation of the curriculum 2013on the component activities introduction (33,33%).Thus, it can be concluded that the ability of a teacher in drawing up the RPP including good (80,21%) and observation of learning at the time of implementation of the RPP IPA including the good (71,43%). Keywords : curriculum 2013, science learning, ability of teacher's, preparation of RPP, implementation of RPP